AN 80-cm UNIVERSAL AZIMUTHAL TELESCOPE FOR AES OBSERVATIONS - Medvedev, Yu. A.; Fashchevsky, N. N.; Chaichuk, R. A.; Paulin, L. S.; Bondarenko, Yu. N. (Одеські астрономічні публікації, 2017)
Based upon altazimuthal mounting SKT 1-70 an 80-cm telescope is being built for photometric and position observations of low- and high- orbital AES. The telescope has two foci: a prime focus for panorama light detectors, and a Cassegrain focus for a photometer.